Analisis Minat Belajar Siswa dan Implikasinya Terhadap Layanan Bimbingan dan Konseling - Nisa, Afiatin; Renata, Dian (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2018)
The aim of this study is to find out students learning interest and its implication toward counseling and guidance service. Research method used is descriptive qualitative. The data taken by questionnaire, observation and interview. There are 30 question on the questionnaire given to 45 students.The questionnare is given to the respondents of counseling and guidance teacher, headmaster, and students. Observation is done by observing the learning process. Data analysis technique is done by collecting, grouping, analyzing, and interpreting the data. The result shows that the analysis of students learning interest and its implication toward counseling and guidance service is in Good Category.